2004
DOI: 10.1111/j.1748-7692.2004.tb01187.x
|View full text |Cite
|
Sign up to set email alerts
|

TEMPORARY THRESHOLD SHIFTS AFTER NOISE EXPOSURE IN THE BOTTLENOSE DOLPHIN (TURSIOPS TRUNCATUS) MEASURED USING EVOKED AUDITORY POTENTIALS

Abstract: The time course of recovery from temporary threshold shift (TTS) was measured in a bottlenose dolphin, Tursiops truncatus, using an evoked‐potential procedure. The envelope‐following response (EFR), which is a rhythmic train of auditory brainstem responses (ABR) to sinusoidally amplitude‐modulated tones, was used as an indicator of the sound reception by the animal. Variation of the intensity of the stimulus allowed us to measure the animal's hearing via EFR thresholds. During each session, following an initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 18 publications
4
67
1
1
Order By: Relevance
“…Several investigations in odontocetes have confirmed this regularity. Despite the variety of experimental conditions, the investigations have indicated that the highest TTS appeared at test frequencies above the fatiguing sound frequency, roughly 0.5 to 1octave Nachtigall et al, 2004;Finneran et al, 2007;Lucke et al, 2009;Mooney et al, 2009;Popov et al, 2011).…”
Section: Across-frequency Spread Of Ttsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigations in odontocetes have confirmed this regularity. Despite the variety of experimental conditions, the investigations have indicated that the highest TTS appeared at test frequencies above the fatiguing sound frequency, roughly 0.5 to 1octave Nachtigall et al, 2004;Finneran et al, 2007;Lucke et al, 2009;Mooney et al, 2009;Popov et al, 2011).…”
Section: Across-frequency Spread Of Ttsmentioning
confidence: 99%
“…These investigations have demonstrated variable durations of TTS recovery, depending on the experimental conditions and initial TTS value. In the first evoked-potential TTS investigation in T. truncatus (30min noise exposure of 4-11kHz bandwidth, 160dBre.1μPa), a TTS of 8dB at 5min after exposure (the earliest time point) recovered at a rate of ~1.5dB per time doubling, completing recovery in less than 1h (Nachtigall et al, 2004). A higher TTS (up to 40-45dB) revealed by the evokedpotential method after exposure to a 20kHz tone of [186][187][188][189][190][191][192][193][194] 2 s) resulted in almost no recovery within the first hour after exposure, requiring up to 4days for a complete recovery (Finneran et al, 2007).…”
Section: Tts Timingmentioning
confidence: 99%
“…The use of AEP techniques to measure hearing sensitivity of odontocetes has become increasingly popular (e.g. Popov and Supin, 1990a;Popov and Supin, 1990b;Szymanksi et al, 1999;Andre et al, 2003;Nachtigall et al, 2004;Yuen et al, 2005;Cook et al, 2006;Houser and Finneran, 2006a;Mooney et al, 2008;Nachtigall et al, 2008;Mooney et al, 2009). Thus, a powerful tool to learn more about the hearing of live-stranded cetaceans, particularly those that are rare or endangered, would be to combine CT imaging and AEP techniques.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed, the findings shown in Table 3 appeared to be at odds with the findings of the Horizon scan, see Figure 4. However, when we considered the content of the articles identified, it was notable that although there were a significant number of publications the research effort appears to center around only a few species: for example, killer whales (Erbe, 2002;Morton and Symonds, 2002;Holt et al, 2009;Wieland et al, 2010;Williams et al, 2014b;Samarra et al, 2015;Houghton et al, 2015; and bottlenose dolphins Buckstaff, 2004;Nachtigall et al, 2004;Luis et al, 2014;Bas et al, 2015;Gospić and Picciulin, 2016). Perhaps un-coincidentally these are also two species that we have more knowledge pertaining to their hearing capabilities due to research conducted on captive animals.…”
Section: Discussionmentioning
confidence: 99%